Gratification levels among farmers on information disseminated through agricultural television programs in Malaysia - Azarian, Zoheir Sabaghpour (2013)
The agriculture industry like most developing countries plays a substantial function in Malaysia. Agricultural activities shape the basic infrastructure of rural life, contributing significantly to the condition of rural communities in terms of business opportunities, employment and quality of the environment. In order to increase agricultural production, farmers ought to make their own decision, understand agricultural issues clearly and answer questions relevant to agricultural production. To attain this, farmers must be connected with proper information and knowledge in accurate format that will aid them in gratifying their information needs. It is now generally accepted that mass media could play a major role in dissemination of agricultural information. This study, based on the concept of Expectancy-value Model, has the following objectives, (1) to determine the level of consumption on television agricultural programs among farmers, (2) to determine the farmer‟s beliefs and evaluation towards television agricultural programs in fulfilling their information needs, (3) to identify the credibility level of television agricultural programs, (4) to determine the perceived gratification sought and gratification obtained by the farmers from the television agricultural programs in fulfilling their information needs, (5) to determine the relationship between farmer‟s beliefs, evaluation and credibility assessment towards television agricultural programs and gratification obtained (GO), (6) to examine to what extent gratification sought (GS) mediates the relationship between beliefs, evaluation, credibility assessment and gratification obtained (GO), (7) to examine to what extent media consumption mediates the relationship between beliefs, evaluation, credibility assessment and gratification obtained (GO). A quantitative method is employed for this study. The data were collected from a total of 400 respondents representing the farmers who were selected base on four zones in peninsular Malaysia (Northern, Central, Southern and East Coast Zone). Each of the zone selected was represented by a state in which has the highest of mass media owners. For sampling procedure, stratified random sampling was utilized. Statistical analysis methods (SPSS) and Structural Equation Modeling (SEM) were used for analysis the data. The findings indicated that TV agricultural programs were believed to possess the characteristics of keeping their viewers up-to-date on latest information pertaining crops/livestock/ agriculture. Results from this study also showed that farmers‟ gratification obtained towards television agricultural programs were moderate. The results of the SEM revealed that the full mediation model explained the data better than the indirect structural model. Moreover, the results indicated that eight of the ten hypotheses proposed were supported by statistically significant results. According to the results, all direct relationships were supported, and all indirect effects were also supported, except the mediating effects of perceived gratification sought and media consumption were not found to be a mediator between “Credibility” and “perceived gratification obtained”. The findings of this study, therefore, could be useful to extension agents, policy makers, and media program implementers by providing a better understanding of the strengths and weakness of their strategies.